Observing another in pain facilitates vicarious experiences and modulates somatosensory experiences - Vandenbroucke, Sophie; Crombez, Geert; Loeys, Tom; Goubert, Liesbet (Frontiers in Human Neuroscience, 2014)
Objective: This study investigated whether individuals reporting vicarious pain in daily life (e.g. the self-reported vicarious pain group) display vicarious experiences during an experimental paradigm, and also show an improved detection of somatosensory stimuli while observing another in pain. Furthermore, this study investigated the stability of these phenomena. Finally, this study explored the putative modulating role of dispositional empathy and hypervigilance for pain. Methods: Vicarious pain responders (i.e., reporting vicarious pain in daily life; N=16) and controls (N=19) were selected from a large sample, and viewed videos depicting pain-related (hands being pricked) and non-pain related scenes, whilst occasionally experiencing vibrotactile stimuli themselves on the left, right or both hands. Participants reported the location at which they felt a somatosensory stimulus. We calculated the number of vicarious errors (i.e., the number of trials in which an illusionary sensation was reported while observing pain-related scenes) and detection accuracy. Thirty-three participants (94.29%) took part in the same experiment five months later to investigate the temporal stability of the outcomes. Results: The vicarious pain group reported more vicarious errors compared with controls and this effect proved to be stable over time. Detection was facilitated while observing pain-related scenes compared with non-pain related scenes. Observers’ characteristics, i.e., dispositional empathy and hypervigilance for pain, did not modulate the effects. Conclusion: Observing pain facilitates the detection of tactile stimuli, both in vicarious pain responders and controls. Interestingly, vicarious pain responders reported more vicarious errors during the experimental paradigm compared to controls and this effect remained stable over time.